Polar lows and their effects on sea ice and the upper ocean in the Iceland, Greenland and Labrador Seas - Gutjahr, Oliver; Mehlmann, Carolin (ESS Open Archive, 2023)
Based on two case studies, we show for the first time that explicitly resolving polar lows in a global climate model (ICON-Sapphire) with a high resolution of 2.5 km in all components (atmosphere, ocean, sea ice and land) leads to strong heat loss from the ocean near the sea ice edge and from leads and polynyas in the ice cover. Heat losses during marine cold air outbreaks triggered by polar lows lead to the formation of dense water in the Iceland and Greenland Seas that replenishes the climatically important Denmark Strait Overflow Water (DSOW). Further heat losses and the rejection of brine during ice formation in polynyas, such as the Sirius Water Polynya in northeast Greenland, contribute to the formation of dense water over the Greenland shelf. In the Labrador Sea, polar lows intensify cold air outbreaks from the sea ice and quickly deepen the ocean mixed layer by 100 m within two days. If mesoscale polar lows and kinematic features in the sea ice are not resolved in global climate models, heat loss and dense water formation in (sub-)polar regions will be underestimated.